Hubungan Self Esteem Dengan Perilaku Asertif Pada Siswa Di SMA 10 Tana Toraja - Triwidaryanty; Andi Asrina; Fairus Prihatin Idris (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
Teenagers often face internal problems that they are not aware of, which can then cause conflict due to self-esteem problems. Teenagers with high self-esteem will think positively about things in themselves, in contrast to teenagers who have low self-esteem will think negatively about themselves and do not like the perception of everything around them. This study aims to determine the relationship between self-esteem and assertive behavior in students at SMA 10 Tana Toraja in 2025. This type of research is a quantitative approach with a cross-sectional design. We used a Purposive Sampling technique to select a sample of 118 students. Data were collected using a questionnaire and analyzed using univariate and bivariate analyses, including the chi-square test. The chi-square test is a statistical test that measures the association between two categorical variables. The results of this study show that there is a relationship between self-esteem (power) (p = 0.000) with assertive behavior, there is a relationship between self-esteem (Significance) (p = 0.001) with assertive behavior, there is a relationship between self-esteem (Virtue) (p = 0.001) with assertive behavior, there is a relationship between self-esteem (Competence) (p = 0.003) with assertive behavior in students at SMA 10 Tana Toraja. For students of SMA 10 Tana Toraja, it is hoped that they can improve their abilities in the field of competence, improve public speaking skills, skills in extracurricular areas, and increase concern among fellow students.